The Effect of Fossil Fuel Subsidy on the Share of Energy Intensive Industries from Total Manufacturing Output in an Economy: A panel regression analysis - Hassan, Omnia (AUC Knowledge Fountain, 2019)
Fossil fuel reform is on the agenda of most countries due to their negative effects on the economy and the environment. Several researches studied the impact of energy prices increase and subsidies removal on macroeconomic variables. Another issue that is less addressed in the literature is the effect of energy subsidies and consequently the effect of their removal on the industrial output structure of the economy. Even the few conducted empirical research focus on the effect of the price of energy not subsidies. This study explores the effect of the level of fossil fuel subsidy on the share of energy intensive industrial output from total output using data from 52 countries across Africa, Asia, Europe, North and South America during the period from 2003 till 2015. This study employs static as well as dynamic panel data analysis, namely Fixed Effects, Feasible Generalized Least Squares, and dynamic Arellano-Bond GMM estimators. The results show that electricity subsidy is the most effective source of energy subsidy in industry followed by coal subsidy where both subsidies cause the share of energy intensive manufacturing output from total manufacturing output to increase. This study provides evidence that electricity and coal subsidies provide a competitive advantage for energy intensive industries and increase their share of contribution to the total manufacturing output. However, this induced competitive advantage may not always help the economy reach the outmost potential. There could be other industries that deserve more support because of their ability to absorb unemployment and increase welfare in the economy. The results also show that countries that have switched to renewable clean sources of energy are countries that have shifted towards less energy intensive industries.